Implementation fidelity and influencing factors of the bottom-up quantification approach for essential medicines in primary health facilities in Tanzania: evidence from four years - William M. Reuben; Selestin J. Ngoma; Idda H. Mosha; Raphael Z. Sangeda (Bulletin of the National Research Centre, 2026)
Abstract Background Bottom-Up Quantification (BUQ) was institutionalized in Tanzania to improve forecasting and the availability of essential medicines by anchoring demand estimates at the health facility level. However, evidence on how faithfully the BUQ has been implemented across primary healthcare facilities, particularly following system automation, remains limited. This study assessed the level of BUQ implementation fidelity and the implementation-related factors associated with fidelity variations across facilities. Methods An explanatory sequential mixed-methods design was used. Quantitative data were collected through a structured facility-level questionnaire administered to members of the Medicines and Therapeutics Committee and other staff involved in BUQ across primary health facilities in seven regions of mainland Tanzania. Data spanned four financial years (2020/2021–2023/2024) and captured implementation experiences. Results A total of 258 study participants were included in the quantitative analysis. The mean overall fidelity score was 70.1 (SD = 22.1), indicating moderate implementation fidelity, with substantial variability across facilities. Fidelity was lowest among dispensaries compared to health centers and council hospitals. Organizational responsiveness was independently associated with higher fidelity (β = 0.215, p = 0.013), while dispensary-level facilities and certificate-level staff education were associated with lower fidelity. Qualitative findings indicated that gaps in training, supervision, feedback mechanisms, staff turnover, and digital system functionality contributed to lower fidelity, particularly at lower levels of care delivery. Conclusion The implementation fidelity of the BUQ in Tanzania was uneven across primary healthcare facilities, with persistent challenges at the dispensary level despite national-scale-up and automation efforts. Strengthening organizational responsiveness, human resource capacity, supervision, and feedback mechanisms is critical for improving fidelity. Differentiated implementation support tailored to the facility context is needed to enhance the effectiveness of the BUQ and strengthen the availability of essential medicines.